2021
DOI: 10.3389/fimmu.2020.603569
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alpha 2 Macroglobulin in IgG-Aggregation and Chronic Activation of the Complement System in Patients With Chronic Lymphocytic Leukemia

Abstract: Chronic lymphocytic leukemia (CLL) is the most common leukemia in adults in the western world. One of the treatments offered for CLL is immunotherapy. These treatments activate various cellular and biochemical mechanisms, using the complement system. Recently it was shown that the complement system in CLL patients is persistently activated at a low level through the classical pathway (CP). The mechanism of chronic CP activation involves the formation of IgG-hexamers (IgG-aggregates). According to recent studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…In a recent study, A2M was also identified as the possible antigen causing hexamerization/aggregation of IgG as seen in patients with chronic lymphocytic leukemia and chronic activation of the complement classical pathway. A2M was found to be part of the IgG hexamer complex and present at the cell surface of malignant B lymphocytes through binding with GRP78 ( 36 ). The mechanism through which such interaction would occur remains to be determined.…”
Section: A2m and The Complement Systemmentioning
confidence: 99%
“…In a recent study, A2M was also identified as the possible antigen causing hexamerization/aggregation of IgG as seen in patients with chronic lymphocytic leukemia and chronic activation of the complement classical pathway. A2M was found to be part of the IgG hexamer complex and present at the cell surface of malignant B lymphocytes through binding with GRP78 ( 36 ). The mechanism through which such interaction would occur remains to be determined.…”
Section: A2m and The Complement Systemmentioning
confidence: 99%
“…Our previous studies that focused on the chronic CP activation in CLL included characterization of the cell-free IgG-aggregates that exist in CLL serum and act as a CP activator (4,16). In the initiation of CP activation, IgGhexamers bind C1, the first component of the CP, and activate a cascade of events until C5b-9 (MAC), the final complement Correlation of the serum A2M levels with complement components.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly evident at advanced CLL stages. Although some of the A2M molecules bind to T-lymphocytes and to the B-lymphocytes via the CD91 receptor (24) and the GRP78 receptor (4,25,26), respectively, the increased amounts of A2M produced, yield serum levels that correlate very well with the lymphocytes' counts in the circulation. In the experiments assessing A2M production by B-cells, the potential binding to the CD91 receptor on Tlymphocytes is irrelevant, since these experiments were performed using only B-cells (in case of cell lines) or 99% pure primary B-cells preparations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations